GMAT® math workbook - Kaplan, Inc. (New York : Kaplan Publishing, 2008)
"Kaplan's GMAT Math Workbook is designed to help you build the essential math skills you'll need for the GMAT. Focused review, practice questions, and test-taking strategies will help you master the material and face the test with confidence. Best used with Kaplan's GMAT Prep Plus. Get both and the GMAT Verbal Workbook in Kaplan's GMAT Complete set. Kaplan is so certain that GMAT Math Workbook offers all the review you need to excel on the test that we guarantee it: After studying with this book, you'll score higher on the Quantitative section of the GMAT--or you'll get your money back. Essential Review: --Review of the math the GMAT tests most --Practice questions for all concepts and question types, with detailed answer explanations --Test-taking strategies for every question type to help you tackle the test efficiently --Strategy sheet with important formulas and tips. Expert Guidance: --We know the test: The Kaplan team has spent years studying every GMAT-related document available. --Kaplan's expert psychometricians ensure our practice questions and study materials are true to the test. --We invented test prep--Kaplan (www.kaptest.com) has been helping students for almost 80 years. Our proven strategies have helped legions of students achieve their dreams."--Amazon.com
From the creator of the #1 GMAT Course--Cover
At head of cover title: Kaplan.
Donated by Farhana Zahir
l
Keywords: Mathematics -- Examinations, questions, etc; Management -- Problems, exercises, etc; Graduate Management Admission Test -- Study guides; Universities and colleges -- Graduate work -- Examinations -- Study guides